2019
DOI: 10.1016/j.rbmo.2018.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Individualization of the starting dose of follitropin delta reduces the overall OHSS risk and/or the need for additional preventive interventions: cumulative data over three stimulation cycles

Abstract: In total, 37 sites from 11 countries (see Appendix) participated in ESTHER-1 and 32 of the 37 sites participated in ESTHER-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 24 publications
7
33
0
Order By: Relevance
“…After a secondary analysis of ESTHER-1, Fernández-Sánchez et al confirmed that individualized dosing with follitropin δ significantly reduced moderate/severe OHSS and/or the need of OHSS preventive interventions in patients undergoing up to three COS cycles, and the greatest benefit was observed in patients in the highest AMH quartile, those with the maximal risk of severe OHSS [ 43 ].…”
Section: Recombinant Human Fsh (R-hfsh)mentioning
confidence: 99%
“…After a secondary analysis of ESTHER-1, Fernández-Sánchez et al confirmed that individualized dosing with follitropin δ significantly reduced moderate/severe OHSS and/or the need of OHSS preventive interventions in patients undergoing up to three COS cycles, and the greatest benefit was observed in patients in the highest AMH quartile, those with the maximal risk of severe OHSS [ 43 ].…”
Section: Recombinant Human Fsh (R-hfsh)mentioning
confidence: 99%
“…Addition of hp-hMG on day of antagonist initiation significantly lowers OHSS rates [8]. In sequential ovarian stimulation cycles, individualized doses of follitropin delta decreased the risk of moderate/severe OHSS than conventional follitropin alfa regimen [9].…”
Section: Introductionmentioning
confidence: 99%
“…OHSS is an iatrogenic complication of ovarian stimulation that is potentially life threatening [8]. A challenge for fertility specialists is prevention and finding a balance between ovarian stimulation for a successful outcome and reducing the patient's risk of OHSS [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…OHSS is an iatrogenic complication of ovarian stimulation that is potentially life threatening [8]. A challenge for fertility specialists is prevention and finding a balance between ovarian stimulation for a successful outcome and reducing the patient's risk of OHSS [8,11]. As a result, certain characteristics and diagnostic markers of a patient's ovarian reserve, namely AMH, are used to identify the patients at risk of developing OHSS and individualize the starting dose of gonadotropin [8,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation